The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/14756366.2016.1178638
|View full text |Cite
|
Sign up to set email alerts
|

Pyridothiadiazine derivatives as aldose reductase inhibitors having antioxidant activity

Abstract: A series of aldose reductase (ALR2) inhibitors based on pyridothiadiazine were prepared and evaluated for their activities in ALR2 inhibition, DPPH scavenging, and MDA inhibition. Comparison studies were carried out between analogs having either hydroxyl or methoxy groups substituted on the N2-benzyl side chains of the compounds. Most of the hydroxy-substituted compounds were found to be more potent compared to their methoxy-substituted analogs with respect to DPPH inhibition (>93%) and MDA inhibition (>73%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Our findings are consistent with Zhu et al. (2016), who found that, with varied degrees of efficiency, thiadiazine derivatives prevented the generation of MDA and the thiobarbituric acid reactive substances (TBARS) and decreased the index of lipid peroxidation (Zhu et al., 2016). This agrees with the conclusions drawn using the total antioxidant capacity technique.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with Zhu et al. (2016), who found that, with varied degrees of efficiency, thiadiazine derivatives prevented the generation of MDA and the thiobarbituric acid reactive substances (TBARS) and decreased the index of lipid peroxidation (Zhu et al., 2016). This agrees with the conclusions drawn using the total antioxidant capacity technique.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment with the examined component also showed a noteworthy decline in MDA in kidney tissue by −9.36% (p < .01) and −19.86% (p < .01) in both the therapeutic and preventive groups, separately, equated with the EAC control group. Our findings are consistent with Zhu et al (2016), who found that, with varied degrees of efficiency, thiadiazine derivatives prevented the generation of MDA and the thiobarbituric acid reactive substances (TBARS) and decreased the index of lipid peroxidation (Zhu et al, 2016). This agrees with the conclusions drawn using the total antioxidant capacity technique.…”
Section: Discussionsupporting
confidence: 92%
“…It has been found that AR inhibitors can ameliorate diabetes mellitus . In fact, numerous AR inhibitors have been tested and evaluated . For example, the AR inhibitor zopolrestato can lower acetate utilization in the diabetic heart, indicating increased glucose combustion via the glycolytic pathway and the Krebs cycle, that otherwise is inhibited in diabetes.…”
Section: The Polyol Pathwaymentioning
confidence: 99%
“…The design and use of ALR2 inhibitors having antioxidant activity is a promising strategic approach that is under active consideration [ 82 , 83 , 84 , 85 ]. The multi-target drugs for T2DM treatment is a good strategy as well [ 67 , 86 ].…”
Section: Resultsmentioning
confidence: 99%